An analysis of digital photojournalistic practices: a study of the Sowetan's photographic department - Allan, Christopher (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2003)
Photojournalism in South Africa is in the process of undergoing a shift from an analogue past to a fully digital future. This shift to digital has already been completed by many of the newspapers in the United States of America and Europe, and the new technology is seen to have made fundamental differences in the way that journalists do their job. This thesis attempts to explore the differences brought about, as well as the problems experienced by the photographic department at the Sowetan newspaper as a result of the shift to digital. How the development of technology has affected the photojournalist throughout is focused upon in a brief history of photojournalism and examples of how technology has shaped different aspects of journalism in both a positive and negative manner is considered. Exactly what digital photography is, how it has been integrated into American Photographic departments and the changes that the new technology has prompted are also explained. The manipulation of images in the past as well as the relative ease of digital manipulation are covered and concerns are raised about the future implications of digital manipulation. By conductlng participant observation and holding interviews, research data was compiled which allowed conclusions to be drawn about the impact that the shift to digital had had on the Sowetan photographic department. Intentional and unintentional consequences were expected and revealed in the research. The job of the photojournalist and photographic editor was found to have changed but perhaps not as dramatically as expected. Third world factors such as crime, poverty and lack of education were discovered to have resulted in problems that differed noticeably from those experienced by American and European photographic departments. Some expected difficulties were not experienced at all, while other major obstacles, specifically the repairs that must constantly be made to the digital cameras, continue to hamper the operations of the new digital department. Some understanding of the problems that might be encountered by future photojournalism departments that are considering making the shift to digital are arrived at, in the hope that they may be foreseen and overcome.
Keywords: Sowetan (Johannesburg, -- South Africa); Photojournalism -- South Africa; Photography -- Digital techniques; Photojournalists -- South Africa; Photojournalism -- South Africa -- Moral and ethical aspects